Preparation method and application of PEF / TPU plastic alloy

CN122344395BActive Publication Date: 2026-10-23JIN JIANG AN RUN TEXTILE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610732231.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-26
Publication Date
2026-10-23
Estimated Expiration
2046-05-26

AI Technical Summary

Technical Problem

[0007]本发明旨在解决现有聚呋喃二甲酸乙二醇酯(PEF)韧性不足、拉丝加工性能差的技术问题,提供一种高拉丝性能的PEF/聚酯型TPU共混物及其制备方法

Benefits of technology

[0013]本发明能产生的有益效果包括:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122344395B_ABST
    Figure CN122344395B_ABST
Patent Text Reader

Abstract

The application provides a preparation method and application of a PEF / TPU plastic alloy, and belongs to the technical field of functional polymer material preparation. The PEF / TPU plastic alloy is prepared by melt blending of PEF and thermoplastic TPU, wherein the PEF is prepared by biomass 2,5-furan dicarboxylic acid (FDCA) and biomass ethylene glycol (EG). Compared with pure PEF, the PEF / TPU plastic alloy prepared by the application has higher tensile strength, greater elongation at break and more excellent spinning performance. By accurately controlling the proportion, the PEF / TPU plastic alloy can form an 'island structure', and the addition of excessive TPU can be avoided to affect the performance of the PEF product. Meanwhile, the melt blending scheme is simple in operation and mild in conditions, and is more conducive to achieving the purpose of industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing PEF / TPU plastic alloy and its application, belonging to the field of functional polymer material preparation technology. Background Technology

[0002] Polyethylene furanate (PEF), as an emerging bio-based polyester material, has shown great application potential in packaging materials, fibers, and engineering plastics in recent years due to its use of biomass resources (such as fructose) as raw materials and its higher gas barrier properties, better thermal stability, and superior mechanical properties compared to petroleum-based polyethylene terephthalate (PET). Its application in the fiber field, in particular, is considered one of the important development directions for replacing PET fibers.

[0003] However, PEF faces a key bottleneck in practical processing and applications: its molecular chains are highly rigid, resulting in low elongation at break and insufficient toughness. For example, the elongation at break of PEF chips obtained through conventional polymerization is typically below 20%, exhibiting typical brittle fracture characteristics. This defect is particularly pronounced in fiber processing (such as melt spinning)—insufficient melt strength and easy breakage of filaments severely limit its application in the field of high-quality fibers. Therefore, how to effectively improve the toughness and drawing performance of PEF while maintaining its advantages of high strength and high barrier properties has become a pressing technical challenge in this field.

[0004] To improve the toughness of PEF, existing technologies mainly explore two approaches: one is to introduce flexible segments through copolymerization, and the other is to physically blend with other polymers. While copolymerization modification can improve toughness, it often sacrifices the heat resistance and gas barrier properties of PEF, and the synthesis process is complex and costly. In contrast, melt blending is more promising for industrial applications due to its simple process and controllable cost.

[0005] In terms of blending modification, the problem of poor compatibility between the two phases is often encountered, resulting in excessively large dispersed phase particle size and limited toughening effect. More importantly, existing blending systems mostly focus on improving the impact resistance of materials, failing to systematically address the comprehensive requirements of PEF for high elongation at break and excellent melt flowability in the fiber drawing process.

[0006] Thermoplastic polyurethane elastomer (TPU) is widely used as a toughening modifier due to its excellent elasticity, high elongation at break, and good processing compatibility with various polyester materials. However, there are currently no reports of systematically improving the fiber drawing properties of polyester-based TPU by melt blending it with PEF. Summary of the Invention

[0007] This invention aims to solve the technical problems of insufficient toughness and poor fiber drawing performance of existing polyethylene furanate (PEF), and provides a PEF / polyester-type TPU blend with high fiber drawing performance and its preparation method. By precisely controlling the type of TPU, the addition ratio, and the blending process, an ideal "sea-island" microphase structure is formed in the PEF matrix, thereby significantly improving its elongation at break and endowing it with excellent fiber drawing performance while maintaining the high strength properties of PEF.

[0008] To achieve the above objectives, the present invention adopts the following technical solution: As a first aspect of the present invention, a method for preparing PEF / TPU plastic alloy is provided, comprising: S1: preparing PEF using a stainless steel reactor, adding 2,5-furandicarboxylic acid (FDCA) and ethylene glycol (EG) to the reactor and adding tetrabutyl titanate as a catalyst, purging with nitrogen for protection, gradually raising the temperature to 220°C, maintaining the temperature for 6 hours, and when the reaction system becomes transparent and adheres to the walls, and no water is generated in the collector, starting the polycondensation reaction, adding triphenyl phosphate as a stabilizer, using a vacuum pump to gradually evacuate the vacuum, and adjusting the reaction temperature according to the water output from the collector, finally raising the temperature to 235°C, achieving a vacuum degree below 50 Pa, maintaining the temperature for 6 hours to end the reaction, and obtaining the finished PEF; S2: Immerse the obtained PEF in liquid nitrogen for 3-5 minutes, then take it out and break it up quickly. Then dissolve it in tetrachloroethane and heat it to 70°C for 2 hours to obtain a mixture solution. Then add the mixture solution to an ethanol / triethylamine mixture solution to precipitate, filter, wash, and dry to obtain purified PEF. S3: PEF and polyester TPU are vacuum dried at 90-100℃ for 3-4 hours. Take 50 parts of PEF and 2.5-7.5 parts of polyester TPU and add them to a twin-screw extruder for melt blending. Under nitrogen protection, the temperature is controlled in three stages at 220-225℃ for melt blending with a residence time of ≤2 minutes. The mixture is then granulated through a granulator to obtain a PEF / TPU plastic alloy.

[0009] Preferably, the polyester-type TPU has a hardness of 90-95 Shore A, an elongation at break of ≥300%, and a tensile strength of ≥35 MPa.

[0010] Preferably, in step S2, the ethanol / triethylamine mixed solution is in a weight ratio of 4:6.

[0011] Preferably, in step S3, the feed inlet speed of the twin-screw extruder is 25 rpm, and the main screw speed is 35 rpm; the three-stage stepped temperature control sets the temperature of the feeding section of the twin-screw extruder to 180°C, the temperature of the mixing section to 205°C, and the temperature of the extrusion section to 220°C.

[0012] As a second aspect of the present invention, a plastic alloy prepared according to the preparation method of the PEF / TPU plastic alloy as described above is provided, the plastic alloy being used to prepare composite fiber materials.

[0013] The beneficial effects that this invention can produce include: (1) Excellent balance of stiffness and toughness The process of this invention improves the toughness and strength of the PEF / TPU plastic alloy compared to PEF by adding an appropriate amount of TPU, achieving the best balance between toughness and strength and overcoming the defect of high brittleness of PEF. (2) Good compatibility, no compatibilizer required This invention utilizes the structural similarity between polyester-type TPU and PEF to obtain a stable blend system without the need for compatibilizers, simplifying the formulation, reducing costs, significantly improving processing performance, and making the spinning process more stable: pure PEF has low melt strength and is prone to breakage during high-speed spinning. After adding TPU, the melt strength of the blend is enhanced, and the spinnability is significantly improved. It can be stably and continuously spun at a processing temperature of 220-225℃, effectively solving the technical bottleneck of difficult spinning of pure PEF, and improving production efficiency and product yield. (3) The melt flowability is significantly improved, and the wire drawing performance is excellent. Melt flow rate (MFR) tests show that increased MFR results in lower viscosity and better flowability of the blend during melt spinning, which helps reduce extrusion pressure, decrease breakage rate, and achieve stable continuous filament drawing. This invention perfectly balances improved processability with superior mechanical properties. (4) Good thermal stability and safe processing window TGA analysis showed a mass loss of less than 1.5% at 220°C, indicating no risk of thermal degradation at this temperature. DSC results showed a moderate decrease in crystallinity, indicating that the introduction of TPU did not disrupt the crystalline structure of PEF. This invention achieves toughening modification while maintaining excellent thermal stability, with a safe and reliable processing window. Attached Figure Description

[0014] To further illustrate the technical solution of the present invention, the specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.

[0015] Figure 1 To prepare the 1H NMR spectrum of the purified PEF from Example 2; The results of PEF synthesis were tested using a deuterated trifluoroacetic acid (TFA) system, such as... Figure 1As shown: the characteristic peaks are clear and free from obvious impurity interference. The sharp singlet at 7.68 ppm belongs to the two equivalent aromatic hydrogens on the furan ring, providing direct evidence of the PEF heterocyclic structure; the strong signal at 4.9 ppm corresponds to the methylene hydrogen bonded to oxygen in the ethylene glycol unit, indicating the successful introduction of the ester side chain. The integral ratio of the two peaks, after conversion, conforms to the theoretical hydrogen atom ratio of 1:2, confirming the regularity of the main chain structure. In summary, the sample was successfully synthesized, with high purity and accurate structural characterization, and can be directly used for subsequent molecular weight calculations and performance evaluation.

[0016] Figure 2 These are scanning electron microscope (SEM) images of Example 2 and Comparative Example 1; right Figure 2 (a) and Figure 2 Sample (b) was characterized by scanning electron microscopy (SEM), and the results are shown in the figure. The pure PEF sample exhibits a dense, continuous cross-section and uniform morphology, displaying a typical homogeneous polymer structure with no obvious phase separation or dispersed phase, consistent with the microscopic morphology characteristics of homopolymers. The PEF blend-modified sample forms a typical island-type microstructure, with PEF as the continuous matrix phase and the dispersed phase uniformly distributed in the matrix as submicron to micron-sized particles. The particles are well dispersed, without obvious agglomeration, pores, or other macroscopic defects. This phase structure confirms that the dispersed phase in the blend system has good compatibility with the PEF matrix, and that the mechanical properties of PEF materials can be synergistically controlled through the introduction of the dispersed phase, providing direct microstructural evidence for the effectiveness of the blend modification scheme.

[0017] Figure 3 A comparison graph of thermogravimetric analysis (TGA) curves between Comparative Example 1 (pure PEF) and Example 2; Thermogravimetric analysis (TGA) was performed on pure PEF and PEF / TPU blends. The results showed that neither pure PEF nor the PEF / TPU blends exhibited significant mass loss below 350℃, demonstrating good initial thermal stability. The 5% thermal decomposition temperature (T5%) of pure PEF was approximately 395℃, while that of the PEF / TPU blend was approximately 375℃. At 800℃, the char residue of both was approximately 10%. This indicates that the introduction of TPU did not significantly affect the thermal stability of PEF, and the blends maintained good high-temperature stability and char-forming properties, providing thermal performance assurance for the processing and application of the materials.

[0018] Figure 4 This is a diagram showing the behavior of the mixture prepared in Example 2 when it is artificially broken; The PEF / TPU blend modified material prepared in this embodiment, verified by manual bending tests, showed that the sample could withstand large-angle bending deformation without brittle fracture, only exhibiting reversible bending deformation, demonstrating excellent bending resistance and toughness. This performance stems from the typical refined island-island phase structure formed within the material: rigid PEF serves as the continuous phase matrix, while elastic TPU, with uniform fine particles as the dispersed phase, has a tight interface between the two phases. During bending stress, the TPU dispersed phase effectively inhibits crack initiation and propagation through plastic deformation, craze termination, and energy dissipation, transforming the brittle fracture mode of pure PEF into ductile fracture, significantly improving the material's elongation at break and impact resistance. This achieves synergistic optimization of rigidity and toughness, providing reliable mechanical property assurance for the material's engineering applications. Detailed Implementation

[0019] The present invention will now be described in detail with reference to the embodiments, but the present invention is not limited to these embodiments.

[0020] Unless otherwise specified, the raw materials used in the embodiments of this invention were all purchased through commercial channels.

[0021] Preparation Example 1: Synthesis of PEF PEF was prepared using a stainless steel reactor. 900g of 2,5-furandicarboxylic acid (FDCA) and 580ml of ethylene glycol (EG) were added to the reactor along with 1.7ml of tetrabutyl titanate as a catalyst. Nitrogen gas was introduced for protection, and the temperature was gradually increased to 220℃. The reaction was maintained at this temperature for 6 hours. When the reaction system became transparent and adhered to the walls, and no water was produced in the collector, the polycondensation reaction began. 15g of triphenyl phosphate was added as a stabilizer. A vacuum pump was used to gradually evacuate the system, and the reaction temperature was adjusted according to the water output from the collector. The final temperature was raised to 235℃, and the vacuum level was lower than 50Pa. The reaction was maintained for 6 hours to complete the process, yielding the finished PEF product.

[0022] Preparation Example 2: Purification of PEF The crude PEF product was immersed in liquid nitrogen for 5 minutes and then quickly crushed. The crushed material was dissolved in tetrachloroethane and heated to 70°C for 2 hours to obtain a mixed solution. This solution was slowly added to an ethanol / triethylamine (4:6, wt) mixture to precipitate the product. The precipitate was then filtered, washed, and dried to obtain purified PEF.

[0023] Example 1: Synthesis of PEF / TPU-5 (TPU accounts for 5 wt% of PEF) PEF and TPU were vacuum dried separately at 90℃ for 3 hours. 50 parts of the dried PEF particles and 2.5 parts of the polyester-type TPU particles were taken and mixed evenly. The polyester-type TPU had a hardness of 90-95 Shore A, an elongation at break ≥300%, and a tensile strength ≥35 MPa. The twin-screw extruder was set with a feed speed of 25 rpm and a main screw speed of 35 rpm. The feeding section temperature was set to 180℃, the mixing section temperature to 205℃, and the extrusion section temperature to 220℃. The mixture was added to the twin-screw extruder and melt-blended under nitrogen protection for 1.5 minutes. The extrudate was water-cooled and pelletized to obtain blended particles. After vacuum drying the blended particles at 90℃ for 4 hours, 1A type dumbbell specimens were pressed using a flat vulcanizing machine at 220℃ and 5-6 MPa. Tensile tests were conducted according to GB / T 1040.2 standard at a test speed of 50 mm / min.

[0024] Test results: Tensile strength was 49.2 MPa, and elongation at break was 40%. DSC testing showed that the glass transition temperature of the PEF phase was 86 ℃, and the glass transition temperature of the TPU phase was -27 ℃.

[0025] Example 2: Synthesis of PEF / TPU-10 (TPU accounts for 10 wt% of PEF) Take 50 parts of dried PEF particles and 5 parts of polyester TPU particles, mix them evenly, and follow the same steps as in Example 1. Test results: The tensile strength was 48.1 MPa, and the elongation at break was 75%. DSC testing showed that the glass transition temperature of the PEF phase was 85.2 ℃, and the glass transition temperature of the TPU phase was -22 ℃, with the glass transition temperatures of the two phases being very close.

[0026] Example 3: Synthesis of PEF / TPU-15 (TPU accounts for 15 wt% of PEF) Take 50 parts of dried PEF particles and 7.5 parts of polyester TPU particles, mix them evenly, and follow the same steps as in Example 1. Test results: Tensile strength was 43 MPa, and elongation at break was 80%. DSC testing showed that the glass transition temperature of the PEF phase was 84 ℃, and the glass transition temperature of the TPU phase was -17 ℃.

[0027] Comparative Example 1: Pure PEF After drying, pure PEF particles were vacuum dried at 90℃ for 4 hours. Then, type 1A dumbbell-shaped specimens were pressed using a flat vulcanizing machine at 220℃ and 5~6MPa. Tensile tests were conducted at a test speed of 50 mm / min according to GB / T 1040.2 standard. Test results: Tensile strength was 52.3 MPa, and elongation at break was 5%. DSC testing showed that the glass transition temperature was 86.5 ℃ and the melting point was 215 ℃.

[0028] Comparative Example 2: PEF / Polyether-type TPU Take 50 parts of dried PEF particles and 5 parts of polyether-type TPU particles, and mix them evenly. The remaining steps are the same as in Example 1; Test results: Tensile strength was 38.6 MPa, and elongation at break was 35%.

[0029] Comparative Example 3: PEF / Polycaprolactone-based TPU Take 50 parts of dried PEF particles and 5 parts of polycaprolactone-type TPU particles, and mix them evenly. The remaining steps are the same as in Example 1; Test results: Tensile strength was 41.2 MPa, and elongation at break was 30%.

[0030] Comparative Example 4: Pure Polyester TPU After drying, polyester TPU particles were vacuum dried at 90℃ for 4 hours. Then, 1A type dumbbell specimens were pressed using a flat vulcanizing machine at 220℃ and 5-6 MPa. Tensile tests were conducted at a test speed of 50 mm / min according to GB / T 1040.2 standard. Test results: Tensile strength was 36.0 MPa, and elongation at break was 350%.

[0031] Specific tensile performance tests are shown in Table 1, and DSC thermal analysis data are shown in Table 2. To evaluate the extrusion processing performance of the material, especially the stability of the melt spinning process, the MFR of pure PEF (Comparative Example 1) and blends with different polyester-type TPU contents (Examples 1-3) were tested at 220℃ and a load of 2.16 kg. The results are shown in Table 3.

[0032] The melt flow rate (MFR) of pure PEF was 8.5 g / 10 min, indicating high melt viscosity and poor flowability. With the addition of polyester-based TPU, the MFR of the blend gradually increased: 10.8 g / 10 min in Example 1 (5% TPU), 13.5 g / 10 min in Example 2 (10% TPU), and 15.0 g / 10 min in Example 3 (15% TPU). Referring to Tables 1 and 2, the Tg of pure PEF was 86.5 °C. With increasing TPU content, the Tg of the PEF phase in Examples 1-3 gradually decreased from 86.0 °C to 84.0 °C, while the Tg of the TPU phase significantly increased from -27.0 °C to -17.0 °C. The close proximity of the two phases' Tg values ​​indicates partial compatibility between the polyester-based TPU and PEF, and strong interactions (such as hydrogen bonds) between the molecular chains of the two phases. This is the fundamental reason why the blend's mechanical properties are superior to other types of TPU.

[0033] The crystallization temperature (Tc) of the blend decreased from 136.5°C for pure PEF to 128.2°C in Example 3, and the crystallinity (Xc) decreased from 29.2% to 24.7%, a moderate decrease. This indicates that the introduction of TPU moderately inhibited PEF crystallization, which is beneficial for improving the transparency and toughness of the material, but did not destroy the basic crystalline structure of PEF, thus ensuring the heat resistance of the material. The melting point of all examples remained at 211-212°C, which is basically consistent with that of pure PEF (215°C), indicating that the thermal stability of the blend was not significantly impaired. With the increase of TPU content, the MFR values ​​of Examples 1-3 increased to 10.8, 13.5, and 15.0 g / 10min, respectively. The increase in MFR means that the blend has lower viscosity and better flowability in the molten state, which can pass through the spinneret orifice more smoothly, reduce extrusion pressure, and reduce the breakage rate, thereby achieving stable and efficient melt spinning.

[0034] In summary, the PEF / polyester-type TPU blends provided by this invention (especially Example 2) achieve an excellent balance in three aspects: mechanical properties (elongation at break increased to 75%, and strength not significantly reduced compared to pure PEF in Example 3 and Comparative Example 1, resulting in superior mechanical properties), thermal properties (Tg of the two phases are close to each other, and Tm is stable), and processing fluidity (significantly improved MFR). Example 2, by sacrificing only 8% of strength and 15% of modulus, increases toughness by 15 times, achieving the ideal effect of "rigidity-toughness balance," and is the optimal embodiment of this invention. Compared with pure PEF, it successfully solves the bottleneck of its high brittleness and difficulty in fiber drawing; compared with polyether-type or polycaprolactone-type TPU blends, this invention utilizes the structural similarity between polyester-type TPU and PEF to obtain better compatibility and superior overall performance.

[0035] As a second aspect of the present invention, a practical technical solution is provided for applying PEF / TPU plastic alloy to the field of textile fibers, which provides a feasible solution for the industrial application of PEF in the fields of fibers and films.

[0036]

[0037]

[0038]

Claims

1. A method for preparing a PEF / TPU plastic alloy, characterized in that: S1: PEF is prepared using a stainless steel reactor. 2,5-furandicarboxylic acid (FDCA) and ethylene glycol (EG) are added to the reactor along with tetrabutyl titanate as a catalyst. Nitrogen gas is introduced for protection, and the temperature is gradually raised to 220°C. The reaction is maintained at this temperature for 6 hours. When the reaction system becomes transparent and adheres to the walls, and no water is produced in the collector, the polycondensation reaction begins. Triphenyl phosphate is added as a stabilizer. Vacuum pumps are used to gradually evacuate the system, and the reaction temperature is adjusted according to the amount of water coming out of the collector. Finally, the temperature is raised to 235°C, and the vacuum degree reaches below 50 Pa. The reaction is maintained for 6 hours to complete the process and obtain the finished PEF. S2: Immerse the obtained PEF in liquid nitrogen for 3-5 minutes, then take it out and break it up quickly. Then dissolve it in tetrachloroethane and heat it to 70°C for 2 hours to obtain a mixture solution. Then add the mixture solution to an ethanol / triethylamine mixture solution to precipitate, filter, wash, and dry to obtain purified PEF. S3: PEF and polyester TPU are vacuum dried at 90-100℃ for 3-4 hours. Take 50 parts of PEF and 2.5-7.5 parts of polyester TPU and add them to a twin-screw extruder for melt blending. Under nitrogen protection, the temperature is controlled in three stages at 220-225℃ for melt blending with a residence time of ≤2 minutes. The mixture is then granulated through a granulator to obtain a PEF / TPU plastic alloy. In step S3, the feed speed of the twin-screw extruder is 25 rpm, and the main screw speed is 35 rpm; the three-stage stepped temperature control sets the temperature of the feeding section of the twin-screw extruder to 180℃, the temperature of the mixing section to 205℃, and the temperature of the extrusion section to 220℃.

2. The method for preparing the PEF / TPU plastic alloy according to claim 1, characterized in that: The polyester-type TPU has a hardness of 90-95 Shore A, an elongation at break of ≥300%, and a tensile strength of ≥35 MPa.

3. The method for preparing the PEF / TPU plastic alloy according to claim 1, characterized in that: In step S2, the weight ratio of the ethanol / triethylamine mixed solution is 4:

6.

4. A plastic alloy prepared by the method for preparing PEF / TPU plastic alloy according to any one of claims 1-3, characterized in that: This plastic alloy is used to prepare composite fiber materials.